Behaviorism category of individual Behavior profile - Anggriani, Novita (Indonesian Journal Education, 2023)
The purpose of this study is to describe behavioristic theory, which is a theory that prioritizes changes in individual behavior as a result of stimulus and response. In other words, learning that is done by each individual is a form of change experienced by students in terms of their abilities which aim to change behavior by way of interaction between stimulus and response. According to Watson, student behavior is the result of genetic inheritance and environmental influences, whereas according to Pavlov it refers to a number of training procedures between one stimulus and a stimulus appearing to replace another stimulus in developing a response. Finally, according to Skinner, the relationship between stimulus and response occurs through interaction with the environment. which then causes a change in behavior. Thus, behavioristic learning theory focuses more on developing individual behavior in a better direction